2008
DOI: 10.2139/ssrn.1018382
|View full text |Cite
|
Sign up to set email alerts
|

Mental Accounting and Small Windfalls: Evidence from an Online Grocer

Abstract: a b s t r a c tWe study the effect of small windfalls on consumer spending decisions by comparing the purchases online grocery customers make when redeeming $10-off coupons with the purchases they make without coupons. Controlling for customer fixed effects and other variables, we find that grocery spending increases by $1.59 when a $10-off coupon is redeemed. The extra spending associated with coupon redemption is focused on groceries that a customer does not typically buy. These results are consistent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Such mental accounting can also occur at the level of individual expenditure categories. For example, Milkman and Beshears (2009) document a flypaper effect-money sticks where it hits-with shopping coupons.…”
Section: Purchases Of Durablesmentioning
confidence: 99%
“…Such mental accounting can also occur at the level of individual expenditure categories. For example, Milkman and Beshears (2009) document a flypaper effect-money sticks where it hits-with shopping coupons.…”
Section: Purchases Of Durablesmentioning
confidence: 99%
“…By using an incentivized laboratory experiment, we exclude this possibility. Fourth, the only existing studies investigating consumption decisions in incentivized environments analyze how people spend a gift or a windfall gain (e.g., Bodkin 1959, Arkes et al 1994, Milkman & Beshears 2009). Most windfall gains are negligibly small compared to life-time wealth and should not alter spending behavior if customers treat wealth and windfall gain as fungible; but these studies find that people spend more after receiving a gift or windfall gain.…”
Section: Introductionmentioning
confidence: 99%
“…On mental accounting, Arkes et al (1994) and Milkman and Beshears (2008) have shown that consumers in laboratory experiments spend more out of their unexpected income than that out of anticipated income. Propensity to spend windfall income is larger than that to regular income and the former decreases as the windfall size increases (Bodkin, 1959;Bird & Bodkin, 1965;Keeler et al 1985).…”
Section: Traders' Psychologymentioning
confidence: 99%